Standardized digital solution with surgical procedure manager (SPM®)—an opportunity for maximizing patient safety and efficiency in ileostomy reversal? - Strobel, Rahel M.; Schineis, Christian H. W.; Lasierra Viguri, Leyre; Stroux, Andrea; Eschlböck, Sophie M.; Lobbes, Leonard A.; Pozios, Ioannis; Seifarth, Claudia; Weixler, Benjamin; Kamphues, Carsten; Beyer, Katharina; Lauscher, Johannes C. (Frontiers in Surgery, 2023)
Background Standardization and digitalization are getting more and more essential in surgery. Surgical procedure manager (SPM®) is a freestanding computer serving as a digital supporter in the operating room. SPM® navigates step-by-step through surgery by providing a checklist for each individual step. Methods This was a single center, retrospective study at the Department for General and Visceral Surgery at Charité – Universitätsmedizin Berlin, Campus Benjamin Franklin. Patients who underwent ileostomy reversal without SPM® in the period of January 2017 until December 2017 were compared to patients who were operated with SPM® in the period of June 2018 until July 2020. Explorative analysis and multiple logistic regression were performed. Results Overall, 214 patients underwent ileostomy reversal: 95 patients without SPM® vs. 119 patients with SPM®. Ileostomy reversal was performed by head of department/attendings in 34.1%, by fellows in 28.5% and by residents in 37.4%; p=0.91. Postoperative intraabdominal abscess emerged more often in patients without SPM®: ten (10.5%) patients vs. four (3.4%) patients; p = 0.035. Multiple logistic regression showed a risk reduction for intraabdominal abscess (Odds ratio (R) 0.19 (95% confidence interval (CI) 0.05 – 0.71); p=0.014) and for bowel perforation (OR 0.09 (95% CI 0.01 – 0.93); p=0.043) in the group with use of SPM® in ileostomy reversal. Conclusions SPM® provides a digital solution for standardization in the visceral surgery operating room. SPM® may reduce postoperative complications in ileostomy reversal such as intraabdominal abscess and bowel perforation. SPM® led to a significantly higher patient safety in this study.